Pengaruh pembiayaan musyarakah, pembiayaan ijarah dan piutang qardh terhadap laba bersih PT. Bank Aceh Syariah periode 2017-2023 - Jenni Pri Andini; Muhammad Dayyan; Tajul Ula (Fakultas Ekonomi dan Bisnis Islam IAIN Langsa, 2025)
This research aims to find out the influence of Musyarakah Financing, Ijarah Financing, and Qardh Receivables on Net Profit at Bank Aceh Syariah. The unit of analysis in this research is Bank Aceh Syariah for the 2017-2023 period. The sampling technique used was a documentation technique in the form of written data from institutions, and 84 data samples were obtained from Bank Aceh Syariah. The data analysis technique used in this research is to use Multiple Linear Regression Analysis of Time Series Data and the Classical Assumption Test with the help of the Eviews10 program. The results of this research show that partially (t Test) the variable Musyarakah Financing has a significant positive effect on Net Profit and Ijarah Financing has a significant negative effect on Net Profit, while Qardh Receivables has no significant effect on Net Profit. Simultaneously (F Test), the variables Musyarakah Financing, Ijarah Financing, and Qardh Receivables jointly influence the Net Profit of Bank Aceh Syariah. The adjusted R2 value of 0.112 indicates that the independent variable used in this research has explained the variation in the Bank Aceh Syariah Net Profit variable by 10%, while the remaining 90% is explained by other variables outside the regression model.